Latina women and career barriers due to post-traumatic stress disorder - Pena, Erika Barragan (My University, 2013)
Hispanic Latinas were surveyed in order to establish the effects childhood sexual abuse had on their academic performance, future career choice and success. The findings presented provide some evidence of a contrast between women who were abused as children and those who were not. In support of the literature, findings from the study show the challenges abused women face in terms of career choice due to the long lasting effects of childhood sexual abuse. A small number of participants, time and resource constraints make it difficult to generalize these findings to a wider population. Replications are suggested in order to identify more discriminate information of factors, which may help to alleviate the suffering of this population.
This file was last viewed in Adobe Reader X.
Keywords: Adult child sexual abuse victims; Post-traumatic stress disorder; Hispanic American women--Vocational guidance--Psychological aspects; Hispanic American women--Education (Higher)